Technical Note—Optimal Procurement in Remanufacturing Systems with Uncertain Used-Item Condition - Nadar, Emre; Akan, Mustafa; Debo, Laurens; Scheller-Wolf, Alan (Operations Research, 2023)
The Importance of Considering System Congestion When Acquiring Used Items for Remanufacturing The condition of used items obtained by remanufacturers often varies widely and may only be truly known after an inspection. In “Technical Note–Optimal Procurement in Remanufacturing Systems with Uncertain Used-Item Condition,” Nadar, Akan, Debo, and Scheller-Wolf study the procurement problem by taking into account this pre-inspection uncertainty as well as the quantities of available used items of different quality levels. The authors provide a novel optimal policy structure for a Markov decision process representation of this problem. They prove that the optimal acquisition decision depends on the system congestion level — the total remanufacturing load weighted by the quality levels. Their results show that it becomes less desirable to acquire a used item as the number of available items or the quality level of any available item increases. To prove their results, the authors introduce a new functional characterization that is a relaxation of supermodularity and discrete convexity.